Elevated C-Reactive Protein: Low Quality Sleep as an Inflammation Indicator - Katie Viehmann-Wical; Jerry W. Lee; Seth Wiafe; Matheni Sathananthan; Anna Nelson (Pan-African Journal of Health and Environmental Science)
Background: High inflammation levels and obesity are each linked to worse health outcomes. Low-quality sleep is linked to higher inflammation.